THE EFFECTIVENESS OF REWARD AND PUNISHMENT STRATEGIES IN ENHANCING ENGLISH VOCABULARY ACQUISITION AMONG UNIVERSITY STUDENTS AT UNIVERSITAS ISLAM KEBANGSAAN INDONESIA - Mursyidah, Nelly; Raiyan; Asman, Yunita; Syakbi; Ayunda, Desy Sary (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
Reward and punishment are part of the learning process, both of which are often used as alternatives to motivate learning. This research used a descriptive qualitative approach with research subjects 3 English lecturers and 15 students from three different classes. Data collection was carried out by interviews. The results of the research show that the application of the reward and punishment method to increase students' English vocabulary is very enthusiastic in learning. The reward and punishment method is combined with several games and movements to motivate students to master English vocabulary. Rewards given include scores, praise, applause and handicraft prizes. Meanwhile, punishment repeats what has been learned, doesn't get a score, or doesn't even get a handicraft prize. The advantage of this method is that it fosters a sense of competitiveness and motivates students to learn optimally. Meanwhile, the disadvantage of this method is that it requires more money as a gift, sometimes it becomes a burden for students who are less active and mentally weak, and focuses on active students. Reward dan punishment menjadi bagian dari proses pembelajaran, keduanya sering dijadikan sebagai alternatif untuk memotivasi belajar. Penelitian ini menggunakan pendekatan kualitatif deskriptif dangan subjek penelitian 3 dosen bahasa Inggris dan 15 mahasiswa dari tiga kelas yang berbeda. Pengumpulan data dilakukan dengan wawancara. Hasil penelitian menunjukkan bahwa, penerapan metode reward dan punishment terhadap peningkatan kosa kata bahasa Inggris mahasiswa sangat antusias dalam pembelajaran. Metode reward dan punishment yang dikombinasikan dengan beberapa permainan dan gerakan untuk memotivasi mahasiswa untuk menguasai kosa kata bahasa Inggris. Reward yang diberikan berupa skor, pujian, tepuk tangan, dan hadiah kerajinan tangan. Sedangkan punishment mengulang yang sudah dipelajari, tidak mendapatkan skor, atau bahkan tidak mendapatkan hadiah kerajinan tangan. Kelebihan dari metode ini adalah menumbuhkan rasa kompetitif, dan memotivasi belajar peserta didik secara maksimal. Sedangkan kekurangan dari metode ini adalah membutuhkan biaya lebih sebagai hadiah, terkadang menjadi beban bagi mahasiswa yang kurang aktif dan mental lemah, dan terfokuskan pada mahasiswa yang aktif.